CORRELATION BETWEEN FORGIVENESS AND ADOLESCENCE FRIENDSHIP INTIMACY MODERATED BY GENDER - Aisyah, Heriatul; Agung, Ivan Muhammad (Faculty of Psychology, Diponegoro University, 2020)
Friendship intimacy is one of the critical developing aspects of adolescence. Previous research shows that forgiveness has a vital role in the interpersonal relationship. This research aims to find a correlation between forgiveness and adolescent friendship intimacy based on gender. Researchâ€™s participant consists of 250 teenagers (125 male and 125 female, M = 16.2, SD = .7, with 15-18 years old age range) in a Pekanbaru school. The sample was collected through convenience sampling. This study used the Friendship Intimacy Scale with Î± = .82 and Forgiveness Scale, with Î± = .94. Based on data analysis, a product-moment correlation shows a positive correlation between forgiveness and adolescence friendship intimacy (r = .273, p < .01), which means the higher the level of individual forgiveness is, the higher the friendship intimacy become. The moderator variable analysis shows that gender becomes a relationship moderator variable between forgiveness and adolescence friendship intimacy (p < .01), which means that correlation between forgiveness and friendship intimacy is more substantial on males than females.Â